From Brand to Genre: The Hallmark Movie. (July 2023) - Braithwaite, Andrea
Hallmark movies are a hit. While most broadcast networks in the United States and Canada are struggling to maintain an audience, Hallmark has launched three additional cable networks and services in the past four years. Much of this success can be attributed to Hallmark's investment—both ideological and economic—in the made-for-TV movie, a form of programing that Hallmark has re-popularized and re-branded—and transformed into a genre. To work through my suggestion that we consider the Hallmark movie as a genre, in the same way we can speak productively about the Western or the buddy cop film, I examine: the structure and content of the Hallmark movie formula; the movies' use of studio system-style production practices; and fan discourses and fan-made content. In re-visiting the Hallmark made-for-TV movie as a genre, we can gain greater insight into how both genres and media companies are navigating the digital media environment.